Family group conferencing for children and families: evaluation of implementation, context and effectiveness (Family VOICE). Study protocol - Scourfield, J; Evans, R; Petrou, S; Pallmann, P; Robling, M; Au, K-M; Jones-Williams, D; Lugg-Widger, F; Meindl, M; Schroeder, E-A; Wood, S; Wilkins, D (Public Library of Science, 2024)
Background: Family group conferences (FGCs) in child welfare bring immediate and wider family members together to decide on the best way to meet a child’s needs. Unlike professionally led meetings, the aim is for decisions to be made by or with family members. Qualitative and mixed-method research with FGC participants tends to show positive experiences: most participants feel their voices are heard; FGCs facilitate family-driven solutions and closer relationships—within families and with social workers. Although there is existing literature on FGCs, there is a paucity of robust comparative UK evaluations, i.e., randomised controlled trials or quasi-experimental studies. Comparative studies internationally have focused on a narrow range of outcomes, not recognised the importance of context, and paid little attention to the quality of delivery. Some qualitative studies have considered process and context but there is scant measurement of these. The aims of this study are, firstly, to establish how FGCs improve outcomes for families and what factors vary their quality, and, secondly, to assess longer-term outcomes in terms of service use and associated costs. Methods: Given the importance of process and context, evaluation informed by realist and complex systems approaches is needed. This multi-method evaluation includes a survey of FGC services in all UK local authorities (n = 212) to map service provision; co-design of programme theory and evaluation measures with family members who have experienced an FGC (n = 16–24) and practitioners (n = 16–24) in two sites; a prospective single-arm study of FGC variability and outcomes after six months; and comparison of service use and costs in FGC participants (n≥300 families) and a control group (n≥1000) after two years using a quasi-experiment. Discussion: This is a pragmatic evaluation of an existing intervention, to identify what mechanisms and contexts influence effective process and longer-term outcomes. The study is registered with Research Registry (ref. 7432).